2016
DOI: 10.1038/jhg.2016.74
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype diversity in mitochondrial genome in a Chinese Han population

et al.

Abstract: Investigations into the use of mitochondrial genome (mtGenome) typing by massively parallel sequencing technologies are well underway in many areas, including forensic genetics. Previous studies have demonstrated that mtGenome sequencing data generated from Ion torrent personal genome machine (PGM) system were highly viable and reliable in forensic research. In this study, 145 whole mtGenomes from unrelated Chinese Han population were sequenced using the Ion PGM system. Results showed that 145 distinct haploty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Figure 4A showed the PCA for the first two principal components, which together explained 49.42% of the total variance based on top-level haplogroup frequencies from 13 mitogenome dataset ( Supplementary Table S3 ). Herein, African (African American [ 42 ] and Zambian [ 54 ]) were clustered to the 4th quadrant, distinguishing from Westeurasian, East and Southeast Asian by PC1, whereas East and Southeast Asian (Xibe, Eastern Han Chinese [ 55 ], Northern Chinese Han [ 8 ], Tibetan [ 44 ] and Filipino [ 56 ]) were clustered to the 2nd quadrant, distinguishing from Westeurasian (U.S. Caucasian [ 42 ], Armenian, Azeri, Georgian, Iranian and Turk [ 49 ]) in the 3rd quadrant by PC2. This distribution mirrored the geographical background of populations compared.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4A showed the PCA for the first two principal components, which together explained 49.42% of the total variance based on top-level haplogroup frequencies from 13 mitogenome dataset ( Supplementary Table S3 ). Herein, African (African American [ 42 ] and Zambian [ 54 ]) were clustered to the 4th quadrant, distinguishing from Westeurasian, East and Southeast Asian by PC1, whereas East and Southeast Asian (Xibe, Eastern Han Chinese [ 55 ], Northern Chinese Han [ 8 ], Tibetan [ 44 ] and Filipino [ 56 ]) were clustered to the 2nd quadrant, distinguishing from Westeurasian (U.S. Caucasian [ 42 ], Armenian, Azeri, Georgian, Iranian and Turk [ 49 ]) in the 3rd quadrant by PC2. This distribution mirrored the geographical background of populations compared.…”
Section: Resultsmentioning
confidence: 99%
“…Two publications were identified after filtering using the terms Homo sapiens, sampling method, and sequencing strategy. The two published population studies included 145 Han individuals from southern Shanghai were identified as CHSH [14], and 107 Han individuals from northern Liaoning province were identified as CHLN [15]. The variant call format (VCF) file of all Chinese data from the phase 3 data of the 1000 Genomes Project were downloaded ( ftp://ftp.ncbi.nlm.nih.gov/1000genomes/ ) [16,17], which included individuals from Beijing who identified as CHBJ, Hunan province was identified as CHHN and Fujian province was identified as CHFJ, and the Dai population from Yunnan was identified as CDX.…”
Section: Methodsmentioning
confidence: 99%